Strategi Pengembangan Sumber Daya Manusia dalam Meningkatkan Kinerja Karyawan PT. Pos Indonesia Cabang Karawang - Pratiwi, Nita Juwita; Army, Widya Lelisa; Supriyadi, Supriyadi (Pascasarjana STIE Amkop Makassar, 2024)
Superior human resources are those who are able to make a full contribution to the company and are reflected in the performance and productivity level of employees. Human resource development is an important step to improve the quality of the workforce which includes the development of conceptual and theoretical knowledge as well as the improvement of abilities in carrying out certain tasks. This development is carried out through various initiatives such as training, education, and coaching, all of which aim to strengthen individuals' abilities in achieving organizational goals. The purpose of this study is to find out the implementation of human resource training and identify career development strategies in improving human resource performance at PT. Pos Indonesia (Persero) Karawang branch. This study uses a qualitative descriptive method with data collection through interviews, documentation and observations of several relevant resource persons, such as branch heads and human resource managers. Based on the results of the study, it can be concluded that PT. Pos Indonesia (Persero) Karawang Branch has carried out human resources training effectively, following planning in accordance with the needs of the company and central policies. In terms of education, the company provides opportunities for employees from various levels of education, ranging from high school graduates to master’s degree, in collaboration with the University of Logistics and International Business (ULBI). Career development begins with performance evaluation and is influenced by education, training and work experience. A rigorous recruitment process ensures that employees have the skills required by the company, while periodic training and work motivation through morning briefings and appreciation strengthen work motivation and employee welfare.